Japanese Studies in Britain : A Survey and History - Kornicki, Peter F. (Peter Francis); Cortazzi, Hugh (Book collections on Project MUSE., 2016)
This book takes an in-depth look at the study of Japan in contemporary Britain, highlighting the many strengths but pointing out some weaknesses, while offering a valuable record of the origins and development of Japanese Studies in British universities and other institutions. It has essays by scholars from universities all over Britain.